Analytical study releasing the new of Prodrug (Paracetamol - Naproxen) using Uv-vis spectrophotometric method - Hamad A. Abdullah; Fadam M. Abdoon; Hanaa K. Saleh (Tikrit Journal of Pure Science, 2018)
This study aims to compose an effective ester Prodrug as well as reducing or removing the side effects of it and to Study of Naproxen release from the Prodrug. This is represented by the following steps: Preparing of Naproxen acid chloride from Naproxen by reacting it with Thionyl Chloride then Preparing of ester group from the reaction of hydroxyl group of paracetamol and the acid chloride of Naproxen. The structural formulas of the prepared compounds were characterized using spectral methods (FTIR,H-NMR and C13-NMR) then the studying of the release for the drug was conducted in acidic and basic medium pH (4, 10). The study showed that the speed of release in the basic medium was faster than that in the acidic medium. So most of the release process will take place in the intestine and not in the stomach.